2019
DOI: 10.1016/j.scitotenv.2018.11.258
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of graphene oxide aggregation, retention, and release in quartz sand

Abstract: • GO interaction depended on GO geometry and orientation, roughness, and adsorbed Ca 2+. • GO interacted in a shallow primary minimum under low ionic strength conditions. • Level arms from roughness and graingrain contacts were important for GO retention. • A mathematical model interpreted the aggregation, retention, and release of GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The transfer of colloids among collectors was regarded to be those deposited at the secondary energy minimum [24]. The secondary minimum deposition was found to be a major retention mechanism for colloid retention under unfavorable conditions even under high IS conditions [15,17,[64][65][66].…”
Section: Profiles Of Retained Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of colloids among collectors was regarded to be those deposited at the secondary energy minimum [24]. The secondary minimum deposition was found to be a major retention mechanism for colloid retention under unfavorable conditions even under high IS conditions [15,17,[64][65][66].…”
Section: Profiles Of Retained Particlesmentioning
confidence: 99%
“…The transfer of colloids among collectors was regarded to be those deposited at the secondary energy minimum [24]. The secondary minimum deposition was found to be a major retention mechanism for colloid retention under unfavorable conditions even under high IS conditions [15,17,[64][65][66]. The colloids associated at secondary minima are located at certain distances from the collector surfaces and can translate and rotate along collector surfaces by hydrodynamic shear [47].…”
Section: Profiles Of Retained Particlesmentioning
confidence: 99%
“…The presence of phosphates can also increase the surface charge/chemical heterogeneity on the solid–water interfaces. It has been well demonstrated that the surface heterogeneities of colloids and collectors tend to reduce and/or eliminate energy barriers at electrostatically unfavorable locations, thus inhibiting colloid retention [ 51 , 52 , 53 , 54 ]. Consequently, these surface physicochemical heterogeneities can contribute to the significant sensitivity of PNP transport to phosphate concentration and the deviations of DLVO predictions from BTCs.…”
Section: Resultsmentioning
confidence: 99%
“…Analytically pure quartz sand (Tianjin Guangfu Fine Chemical Research Institute, Tianjing, China) was used as porous media. The sand was purified by washing in tap water, followed by soaking in HNO 3 (65%) and H 2 O 2 (10%) for 24 h [ 54 ]. Later, the sand was washed with water again, followed by soaking in 100 mM NaCl and ultrapure water (pH 10) with ultrasonication to remove the potential attached colloidal impurities by cation exchange and expand the electrical double layer.…”
Section: Methodsmentioning
confidence: 99%
“…189) of the flowing solution. However, in the case of rGO, the flowing solution with a higher pH exerted higher mobility due to steric hindrance 187 while GO mobility has been shown to be enhanced under lower IS conditions 184,185,189–191 with one exception where a lower IS resulted in decreased mobility. 188 The presence of organic matter ( e.g.…”
Section: Fate and Transport Of Gnms In Soilmentioning
confidence: 99%